Analisis Penerapan Standar Akuntansi Keuangan Entitas Mikro Kecil dan Menengah (SAK EMKM) pada Laporan Keuangan Badan Usaha Milik Desa (BUM Desa) Perkebunan Bukit Lawang Kecamatan Bahorok - Selly Febriana; Saparuddin Siregar; Nurul jannah (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2024)
Financial statements are an important tool to obtain information in connection with the presentation of the financial statements of an organization or company in decision-making. BUM Desa is a government program where in recording its finances requires complete financial reports. However, in the presentation of its financial statements, the Bukit Lawang Plantation Village BUM has limitations in recording it. The purpose of this study is to find out the presentation of BUM Village financial statements and the application of Financial Accounting Standards based on SAK EMKM. The method used in this study is a qualitative research method. The data collection technique is using observation, interviews, and documentation. The results of this study are from the results of the analysis showing that the presentation of the financial statements of the Bukit Lawang Plantation Village BUM is still simple, namely the journal of outgoing money, incoming money, and balance sheet mutations. In the implementation of SAK EMKM, based on the results of the comparison of criteria between the criteria for SAK EMKM's financial statements and BUM Desa shows that BUM Desa in the presentation of its financial statements has not implemented SAK EMKM.